Marketing Strategies of Ice Cream Companies in India - Verma, Saurabh (International Journal on Orange Technologies, 2024)
Although India is the world's largest milk and dairy products producer, it is surprising to see that ice cream consumption remains low at 400 ml. The Indian ice cream market is expected to grow to over 50% from 2019 to 2022, owing to several factors, including ice cream varieties available for the consumers, such as soft ice cream and hard ice cream. The Indian ice cream market consists of both Indian and international brands. These brands are present across metropolitan cities, small towns, and even rural areas. While big brands account for a significant share of the market in cities, it is mostly the unorganised players contributing significantly to its growth in rural areas.